White shoe : how a new breed of Wall Street lawyers changed big business and the American century - Oller, John (Dutton, an imprint of Penguin Random House LLC, 2019)
The legal profession once operated on a smaller scale<U+2014>folksy lawyers arguing for fairness and justice before a judge and jury. But by the year 1900, a new type of lawyer was born, one who understood business as well as the law. Working hand in glove with their clients, over the next two decades these New York City “white shoe” lawyers devised and implemented legal strategies that would drive the business world throughout the twentieth century. These lawyers were architects of the monopolistic new corporations so despised by many, and acted as guardians who helped the kings of industry fend off government overreaching. Yet they also quietly steered their robber baron clients away from a “public be damned” attitude toward more enlightened corporate behavior during a period of progressive, turbulent change in America.